Radicalização Islâmica no Norte de Moçambique: O Caso de Mocímboa da Praia - Habibe, Saide; Forquilha, Salvador; Pereira, João (Instituto de Estudos Sociais e Económicos (IESE), 2019)
Este artigo analisa o fenómeno da radicalização islâmica no Norte de Moçambique, explorando a complexidade das dinâmicas não só na origem do grupo dos Al-Shabaab como também na estrutura do próprio conflito e violência em Cabo Delgado. Os autores consideram que o fenómeno exige uma pesquisa multidisciplinar aprofundada que tome em conta uma multiplicidade de factores de ordem histórica, social, política, económica e religiosa. Acesso à versão inglesa aqui.
Keywords: *indexed; *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Mocímboa da Praia; GP - Cabo Delgado; L - portuguese / português; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; poverty / pobreza; youth / juventude

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Limits of gender equality: Poor, uneducated Mozambicans less likely to see improvement - Bhoojedhur, Sadhiska; Isbell, Thomas (AFR Barometer, 2019)
Gender equality is enshrined in Mozambique’s Constitution and promoted through its participation in international conventions and treaties as well as its 2004 Family Code, which requires equality in property and family law, including sharing of assets within marriage (International Federation for Human Rights, 2007; UN Women, 2012). During the launch of a National Plan of Action on Women, Peace, and Security in June 2018, the Minister of Gender, Children, and Social Welfare reiterated the government’s commitment to promoting gender equality, emphasizing that equal participation of men and women in all spheres of society is a prerequisite for sustainable development (AllAfrica, 2018). Yet gender disparities are a persistent reality for many women in Mozambique, in forms ranging from child marriage and teen pregnancy to domestic violence and sexual abuse (Cumbe, Materula, Sadler, & Agosta, 2017; Christensen, 2018). According to a United Nations Country Team report (2013), more than half of Mozambican women report having suffered some form of physical, sexual, or psychological violence, and almost three-fourths of girls said they were aware of cases of sexual abuse and harassment in their schools. Mozambique ranks 138th out of 164 countries on the United Nations Development Programme’s (2018) Gender Development Index, and especially in the North and in rural areas, traditional patriarchal values remain strong (Tvedten, 2011). In leadership roles, Mozambican women are better represented than women in many other African countries: 40% of the Mozambican Parliament are women (World Bank, 2018). However, while the Global Gender Gap Report ranked Mozambique No. 1 in Africa in 2008 in terms of economic participation and opportunity, by 2018 the country had dropped to No. 7 (No. 49 in the world) because of setbacks in women’s labour-force participation, particularly in senior and managerial positions (World Economic Forum, 2008, 2018). According to the latest Afrobarometer survey, a majority of Mozambicans think gender equality has been achieved with regard to education, work, and land, and give the government good marks on promoting opportunities for women. However, poor and lesseducated citizens are considerably less likely to perceive progress on gender equality. Moreover, Mozambicans’ support for equality is uneven: While most endorse equality in access to land and political leadership, majorities prioritize men when it comes to getting a job and say families are better off if a woman, rather than a man, takes care of home and children.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; gender / género; poverty / pobreza

Protecção social e poupança em 10 edicões dos desafios: que tipo de protecção social pode Moçambique desenvolver? - Siúta, Moisés S. (Desafios para Moçambique 2019, 2019)
Que tipo de protecção social poderá Moçambique desenvolver sem poupança interna e profundamente dependente da poupança externa? Esta é a questão principal que este artigo pretende discutir. A discussão é feita em dois sentidos: mostrar a importância da pesquisa dentro da qual a pergunta surgiu e mostrar a relevância da relação que a mesma estabelece entre a poupança e a protecção social. No primeiro sentido, a relevância da pesquisa é demostrada na abordagem das limitações e deficiências do sistema e formas de protecção social vigentes em Moçambique, destacando-se os elementos que podem contribuir para melhorar o sistema de protecção social moçambicano, abordados dentro do trabalho de pesquisa do IESE. Em geral, os resultados da pesquisa apontam como principal deficiência do sistema de protecção social em Moçambique a sua incapacidade de fornecer protecção digna aos cidadãos, que se socorrem das suas diversas formas (e.g.: demográfica ou financeira) e mecanismos de funcionamento (e.g.: familiar, comunitário, financeiro público e privado). No segundo sentido, a importância da pergunta principal do artigo é fundamentada teórica e empiricamente por meio da identificação das relações existentes entre a protecção social e a poupança e da forma como essas relações se manifestam no caso particular em Moçambique. Por exemplo, o artigo discute o quadro teórico de análise do papel da poupança no crescimento e desenvolvimento económico (figura 1) e a forma como este influencia e determina o tipo, as formas e a qualidade da protecção social que Moçambique pode oferecer aos seus cidadãos. Além do quadro teórico, recorrendo a dados empíricos dos países do mundo inteiro, busca-se enquadrar a economia e o sistema de protecção social moçambicano e estabelecer a relação entre o tipo, as formas e a qualidade da protecção social com o nível de poupança, crescimento e desenvolvimento económico.
Keywords: *tagged; Ethnographic Studies; G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social; ⛔ No DOI found

‘Goats eat where they are tied up’: illicit and habitual corruption in Mozambique - Tvedten, Inge; Picardo, Rachi (Review of African Political Economy, 2018)
The article shows that corruption is structural and omnipresent in Mozambican society, eﬀectively legitimising corrupt practices at all levels. Using an anthropological approach, it argues that smallscale corruption has the most immediate eﬀects for the urban and rural poor and is so common that it has become an integrated part of daily life, or ‘habitual’. While most of the poor relate to corruption through tacit acceptance and acts of compliance, its practical implications are most severe for the very poorest, who cannot aﬀord to take part in corrupt exchanges and are excluded from vital social relationships and social services. A few case studies included re: Northern Moz.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; corruption / corrupção; institutions / instituições; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social

Moçambique Avaliação de Pobreza: Crescimento Forte, Mas Não Partilhado (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; poverty / pobreza

Mozambique Poverty Assessment: Strong But Not Broadly Shared Growth (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; poverty / pobreza

“Our Lives Mean Nothing” - The Human Cost of Chinese Mining in Nagonha, Mozambique - Amnesty International (Amnesty International, 2018)
This report examines Haiyu’s conduct including what the company did or failed to do in acquiring the right to land for use of mining activity in Nagonha, what it did or failed to do in its operations in Nagonha, and what it did or failed to do in response to the villagers’ demand for compensation and resettlement following the flood. The report looks specifically at the breach of the right to adequate housing and decent living standards ensuing from Haiyu’s destruction of the wetland, and the related destruction of one-fifth of the village by the freak flood. The report also examines the Mozambican Government’s failure to protect, promote and fulfil the right to adequate housing and living standards in the village of Nagonha.
Keywords: *indexed; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; natural resources - mining / recursos naturais - mineração; poverty / pobreza

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Strong but not Broadly Shared Growth. Mozambique Poverty Assessment - World Bank (World Bank, 2018)
Mozambique has recorded strong growth, but many low-income households are missing out on the benefits and policy options to make rowth more inclusive in Mozambique
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; poverty / pobreza

Parte III - Pobreza, Protecção Social e População - Brito, Luís de; Chivulele, Fernanda Massarongo (Economia, Recursos Naturais, Pobreza e Política em Moçambique - Uma colectânea de textos, 2017)
IDeIAS Nº40 Moçambique no Índice de Desenvolvimento Humano: comentários IDeIAS Nº35 Será que crescimento económico é sempre redutor da pobreza? Relexões sobre a experiência de Moçambique IDeIAS Nº80 Vulnerabilidade dos estratos urbanos pobres: caso da pobreza alimentar em Maputo IDeIAS Nº17 Estratégias individuais de sobrevivência de mendigos na cidade de Maputo: engenhosidade ou perpetuação da pobreza? IDeIAS Nº12 Armando Guebuza e a pobreza em Moçambique IDeIAS Nº15 Protecção social no contexto da bazarconomia de Moçambique IDeIAS Nº32 Protecção social inanceira e protecção social demográica: ter muitos filhos, principal forma de protecção social em Moçambique? IDeIAS Nº26 A relatividade da pobreza absoluta e segurança social em Moçambique IDeIAS Nº31 Pobreza em Moçambique põe governo e seus parceiros entre a espada e a parede IDeIAS Nº34 Pauperização rural em Moçambique na 1ª década do século XXI IDeIAS Nº28 Crescimento demográico em Moçambique: passado, presente … que futuro? IDeIAS Nº33 Em que fase da transição demográica está Moçambique IDeIAS Nº45 Moçambique e a explosão demográica”: somos muitos? Somos poucos? IDeIAS Nº37 Envelhecimento populacional em Moçambique: ameaça ou oportunidade? IDeIAS Nº46 Desaios da duplicação da população idosa em Moçambique IDeIAS Nº54 Viver mais para viver pior? IDeIAS Nº65 Por que Moçambique ainda não possui pensão universal para idosos? IDeIAS Nº81 Moçambique: um dos piores países para os idosos. Porquê?
Keywords: G - Mozambique / Moçambique; L - portuguese / português; poverty / pobreza; social protection / proteção social

Economia, recursos naturais, pobreza e política em Moçambique: uma colectânea de textos - Brito, Luís de; Chivulele, Fernanda Massarongo (IESE, 2017)
Neste contexto, o conjunto de textos que compõem a presente colectânea apresenta material útil para a contextualização da situação actual e para o debate dos diferentes problemas que o país enfrenta. As discussões sobre eleições, descentralização, participação, dívida pública, sistema financeiro, crescimento e desenvolvimento económico, dentre outras, que fazem parte da colectânea, informam o debate a nível de praticamente todas as áreas de desafios cruciais que hoje se vivem em Moçambique. Não só são fornecidos pontos relevantes para o debate actual, mas através desta colectânea é possível também fazer um acompanhamento histórico da evolução dos diferentes assuntos e ver como temas actualmente destacados no debate nacional já eram levantados no quadro do trabalho do IESE ao longo dos últimos 9 anos. Por esta via, é igualmente possível questionar até que ponto diferentes análises são usadas e consideradas no debate e na formulação de políticas. A colectânea contém 76 boletins produzidos por investigadores permanentes do IESE e alguns investigadores associados e está subdividida em 5 temáticas. A primeira foca questões ligadas à dívida pública, sistema financeiro e mobilização de recursos. Especificamente, esta parte discute a problemática da dívida pública em Moçambique e suas implicações para a economia, assim como dinâmicas do sector financeiro e mobilização de recursos de forma mais geral. A segunda discute a estrutura e estratégia de crescimento económico e suas implicações, fontes e padrões de investimento privado e ligações económicas existentes na economia. A terceira discute três “P” fundamentais no desenvolvimento económico: pobreza, protecção social e população. A discussão sobre pobreza incide sobre a sua conceptualização e mapeamento e sobre a sua relação com crescimento e governação. Esta discussão continua com a questão da protecção social em Moçambique, tratando aspectos como a pensão universal e as estratégias de protecção social no contexto específico da economia de Moçambique, bem como os desafios demográficos que lhe estão associados. Na quarta parte, os textos tratam da questão dos recursos naturais, seu papel no desenvolvimento, relação de grandes projectos de exploração de terra com o desenvolvimento local e a eficácia dos mecanismos concebidos para reforçar a transparência na exploração de recursos naturais. A última parte discute a questão da descentralização, mecanismos de participação da sociedade civil e questões relativas aos processos eleitorais em Moçambique.
Keywords: *snowball; G - Mozambique / Moçambique; L - portuguese / português; economic development / desenvolvimento económico; natural resources / recursos naturais; poverty / pobreza

Pobreza e Bem-Estar em Moçambique: Quarta Availação Nacional - Inquérito Ao Orçamento Familiar - Iof 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Pobreza e Bem-estar em Moçambique: Resumo da Quarta Availação Nacional - Inquérito ao Orçamento Familiar - IOF 2014/15 (2016)
Este relatório apresenta uma análise abrangente de pobreza e bem-estar, e suas tendências em Moçambique entre 2008/09 e 2014/15. Os dados provêm principalmente do Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15 realizado pelo Instituto Nacional de Estatística (INE). Os resultados deste último inquérito são comparados com os obtidos nos inquéritos anteriores (2008/09, 2002/03 e 1996/97).
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; M - survey / inquérito; Northern PEA; demographics / demografia; poverty / pobreza

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Final Report 2011-2015 - Tvedten, Inge; Tuominen, Minna; Rosário, Carmeliza (ORGUT Consulting AB, 2016)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; institutions / instituições; poverty / pobreza; private sector / setor privado

Reality checks in Mozambique – Building better understanding of the dynamics of poverty and well-being. Year Five, 2015, Sub-Report, District of Lago. - Tvedten, Inge; Putile, Beatriz; José, Barnabé; Paulo, Margarida (ORGUT Consulting AB, 2016)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 5th Sub-Report from the District of Lago, focussing on quantitative expressions of changes in poverty and wellbeing and the role of public institutions since the 1st Reality Check in 2011. An Annual Report is produced each year to summarise the findings and conclusions from the three subreports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Reality checks in Mozambique - Building better understanding of the dynamics of poverty and well-being. Year Four, 2014, sub-report, District of Lago - Tvedten, Inge; Paulo, Margarida; José, Barnabé; Putile, Beatriz (ORGUT Consulting AB, 2014)
The Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. Each Reality Check focusses on a specific theme. This is the 4th Sub-Report from the District of Lago, focusing on the private sector/entrepreneurship. An Annual Report is produced each year to summarise the findings and conclusions from the three sub-reports.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; GD - Lago; L - english / inglês; gender / género; poverty / pobreza

Socio-economic and Community Health Baseline - Anadarko Mozambique (ExxonMobil, 2014)
This chapter outlines the socio-economic and health baseline of areas (both onshore and offshore) potentially affected by the Project. The chapter is structured into a number of sections, as follows: • Sections 9.2 and 9.3 provide a summary of the baseline and sources of information used to compile the baseline, respectively. • Section 9.4 defines the Project Area of Influence, providing both an overview of the geographic characteristics as well as the respective administrative divisions and governance structures. • Sections 9.5 to 9.7 provide an overview of Cabo Delgado Province (an important part of the Area of Indirect Influence) and aims to set the broader social, health and economic context in which the Project will be located. • Sections 9.8 to 9.14 provide a description of the social, health and economic characteristics of the Area of Direct Influence, which includes Palma District and the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.15 provides a description of the cultural and religious profile of the Afungi Project Site and Surrounds (including Senga and Maganja). • Section 9.16 provides an overview of perceptions and expectations about the Project. • Section 9.17 provides an understanding of the shipping movements and types of vessels used within the Study Area. • Section 9.18 details the archaeology and cultural heritage baseline of the Afungi Project Site, based on both primary and secondary data.
Keywords: G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; health / saúde; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year Three, 2013 – Agriculture, Climate and Employment - Tvedten, Inge; Rosário, Carmeliza; Tuominen, Minna; Samuel Jones (ORGUT Consulting AB, 2013)
A series of five “Reality Checks” will take place in the period 2011-2016, focussing on the dynamics of poverty and well-being with a particular focus on good governance, agriculture/climate and energy that are key sectors in Swedish development cooperation with Mozambique. Each Reality Check will be published in the form of one Annual Report and three Sub-Reports from each of the three selected study-sites (see ORGUTa 2011 for more details). More concretely, the “Reality Checks in Mozambique” are expected to: i) Inform the public discussion among key development actors on poverty reduction, especially in the province of Niassa; ii) Contribute to a better understanding of qualitative poverty monitoring methods in Mozambique; iii) Provide Sweden with relevant qualitative data on developments and results from its engagement in Mozambique and support further implementation of its programme in Niassa. The series of studies was initiated by an Inception Report published in August 2011 (ORGUT 2011a). Through that exercise, it was decided that the Reality Checks shall be based on fieldwork in three different Districts/Municipalities in the Province of Niassa that display variations in terms of geographical locations, access to public services and levels of poverty and well-being. The three areas selected were i); the Municipality of Cuamba; ii) the District of Lago and iii) the District of Majune (see Map 1). The 1 st Reality Check was carried out in 2011 in the form of three sub-reports (Orgut 2011 b,c,d) and the first Annual Report (Orgut 2011 e), and represent a baseline upon which the subsequent Reality Checks will build. This is the Annual Report for the 2 nd Reality Check, synthesising the main findings from the Cuamba, Lago and Majune sub-reports. In addition to pursuing the overall issue of the dynamics of poverty and well-being, this year’s reports have a thematic focus on governance.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; institutions / instituições; poverty / pobreza

Youth Social Exclusion and Lessons from Youth Work: Evidence from literature and surveys - Paolini, Giulia; Brel, Patrice; Vanandruel, Colette (European Commission Education, Audiovisual and Culture Executive Agency (EACEA), 2013)
It is widely recognised that social exclusion produces deep and long-term damage to the living conditions, social and economic participation, emotional life, and health status of young people. It also contributes to the intergenerational transmission of poverty. In turn, insecurity in living standards, political and social isolation, feelings of estrangement and unhealthy lifestyles aggravate pre-existing conditions of social exclusion. This results in a vicious circle where socially excluded young people are in even more danger of suffering from additional material deprivation, social and emotional marginalisation, and health issues, which in turn expose them to more serious risks of exclusion. Almost one out of three young persons between the ages of 18 and 24 is at risk of poverty or social exclusion in the European Union. Youth work can offer opportunities for preventing and remedying this vicious circle. By offering young people targeted support, opportunities for non-formal learning, information on health and wellbeing, and opportunities for positive integration into the local community, youth workers are able to reduce the risks of further social exclusion linked to deteriorating living conditions and unhealthy life styles. The EU Youth Strategy recognises the relevance of youth work to mitigating the effects of social exclusion amongst young people. Reaffirming this concept, the Council Resolution on Youth Work of 2010 invited Member States and the Commission to support the development of youth work at local, regional, national and European level. The relation between youth work and social inclusion also touches upon the priorities established by the 2012 EU Youth Report. A general overview of the fundamental threats to social inclusion experienced by young people can be found in the dedicated chapter of the Youth Report. The benefits coming from youth work to the inclusion of young people, and in particular of those with a migrant background, has been recognised in the Conclusions of the Council of 27 November 2012. To address the risks of exclusion run by many young individuals, the Social Investment Package adopted by the European Commission seeks to improve the situation of young people by tackling childhood disadvantage, improving access to quality education and support services, helping young people develop skills relevant to the labour market, and ensuring work experience and on-the-job training and helping young people find a first good job (European Commission, 2013a). This paper aims at offering evidence about the situation of social exclusion suffered by young people in the European Union, and the positive effects that youth work initiatives produce in fostering their (re)inclusion. Looking at factual information on the main conditions of exclusion is essential to have an accurate understanding of the threats encountered by young people. Available data and research literature illustrate the major reasons behind the marginalisation of young Europeans, and pave the way to the development of effective policy strategies to prevent it.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; youth / juventude

Reality checks in Mozambique. 2nd Annual Report - Governance - Tvedten, Inge (ORGUT Consulting AB, 2012)
The Reality Checks are implemented between 2011- 2016, with fieldwork being carried out each year in the Districts of Cuamba, Majune and Lago in the Niassa Province. Sub-Team Leaders are Carmeliza Rosário, Minna Tuominen and Inge Tvedten. This is the Annual Report for the 2nd Reality Check, synthesising the main findings from the three sub- reports. The report is written by the Team Leader for the Reality Checks in Mozambique Dr. Inge Tvedten - with support from Carmeliza Rosário, Minna Tuominen and Aslak Orre (Thematic Advisor).
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; gender / género; governance / governação; poverty / pobreza

Reality checks in Mozambique: building better understanding of the dynamics of poverty and well-being. Annual Report, Year One - Tvedten, Inge (ORGUT Consulting AB, 2012)
he Reality Checks are implemented 2011-2016 and each year field work is carried out in the Municipality of Cuamba, the District of Lago and the District of Majune in the Niassa Province. This is the Annual Report for Year One of the Reality Checks and aims at summarising the conclusions based on the findings from the field sub-report from each study location.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Cuamba; GD - Lago; GD - Majune; GP - Niassa; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; gender / género; poverty / pobreza

Gender and poverty in Mozambique - Tvedten, Inge (CMI, 2010)
Gender equality and women’s empowerment are high on the government and donor agendas in Sub-Saharan Africa, but have largely failed to have an impact. Rather than ‘mainstreaming’ gender, more attention to the variations in the position of women is necessary. In a series of three studies on gender policies and the feminisation of poverty in Mozambique, significant differences were found between the north and the south as well as between rural and urban areas. Such variations are essential to understand in order to design relevant policies and interventions for improving the conditions for women in the country.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; empowerment / empoderamento; gender / género; poverty / pobreza; ⛔ No DOI found

Género e pobreza em Moçambique - Tvedten, Inge (CMI, 2010)
A igualdade de género e o empoderamento das mulheres estão no centro das agendas do governo e dos doadores na África Sub-Sahariana, mas no geral não conseguiram ter impacto. Mais do que a ‘integração’ do género, é necessária mais atenção às variações da posição das mulheres. Numa série de três estudos sobre políticas de género e feminização da pobreza em Moçambique, foram encontradas diferenças significativas entre o norte e o sul, bem como entre as áreas rural e urbana. É essencial que se compreendam estas variações para se desenhar políticas e intervenções relevantes para a melhoria das condições das mulheres no país.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; empowerment / empoderamento; gender / género; poverty / pobreza

‘Opitanha’ Revisited Assessing the Implications of PARPA II in Rural Northern Mozambique 2006-2009 - Tvedten, Inge; Paulo, Margarida; Rosário, Carmeliza (Chr. Michelsen Institute, 2010)
This report is part of the efforts to monitor and evaluate the implications of Mozambique’s Poverty Reduction Strategy PARPA II (GdM 2005). Three qualitative and participatory studies have already been carried out in three different areas of the country: One in the District of Murrupula in Nampula Province (Tvedten, Paulo & Rosário 2006); one in four bairros in the capital Maputo (Paulo, Rosário & Tvedten 2007); and one in the district of Buzi in Sofala Province (Rosário, Tvedten & Paulo 2008). Each of these studies is to be followed up in order to ascertain changes in social relations and cultural perceptions of poverty and well-being, by visiting the same local administrations, the same communities and the same households after a period of three years. This report is the first in the series of the three such follow-up studies, with the Maputo and the Buzi studies planned for 2010 and 2011, respectively.
Keywords: *tagged; G - Mozambique / Moçambique; G - central / centro; G - north / norte; G - south / sul; GD - Murrupula; GP - Maputo; GP - Nampula; L - english / inglês; M - evaluation / avaliação; agriculture / agricultura; education / educação; poverty / pobreza; social inclusion & exclusion / inclusão e exclusão social; urbanization / urbanização

The politics of poverty: Elites, citizens, and states - findings from ten years of DFID-funded research on governance and fragile states 2001-1010 - UK DFID Research and Evidence Staff (UK Department for International Development (DFID), 2010)
This research adds depth to our understanding of development as a political process, provides rich evidence based on country experience, and points to the questions which aid agencies must address in order to be effective – including in more fragile countries. It demonstrates that durable reforms need to be constructed, nationally and locally, in a way that fits each political context and it challenges donors to build the capacity to contribute to this effectively
Keywords: *indexed; *tagged; L - english / inglês; citizenship & participation / cidadania e participação; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; decentralization / descentralização; fragility / fragilidade; governance / governação; poverty / pobreza; taxation / tributação